Filsafat ilmu: Landasan penelaahan ontologi dan aksiologi ilmu - Fu'adi, Eka Agustin (Maliki Interdisciplinary Journal, 2024)
Revealing the basic science used is ontology and axiology, or in other words what and where science is. What is the nature of ontology? who wants to know about the existence or how the nature of the object being studied came to be knowledge. Axiology discusses values ​​related to the usefulness of knowledge, with discussing these two foundations humans will gain a better understanding. The research method used is literature study, with a descriptive analysis approach. The results obtained are that there is a relationship between these two foundations for can provide meaning in ontological and axiological studies of the final research results science, with the aim of providing the desired results from research the. By understanding the meaning of ontology and axiology we can help improve the quality of life and human welfare.